2016
DOI: 10.1556/004.2016.016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antibiotic resistance of Enterococcus strains isolated from poultry

Abstract: The aim of this study was to evaluate the frequency of occurrence of bacteria of the genus Enterococcus in poultry, to identify them by means of matrixassisted laser desorption/ionisation time-of-flight mass spectrometry (MALDI-TOF MS), and to analyse the antimicrobial susceptibility of the isolated strains to the drugs most frequently used in poultry. The material for the bacteriological tests was obtained mainly from the heart (97%) of the birds investigated. Of a total of 2,970 samples tested, 911 (30.7%) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
33
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 39 publications
11
33
1
Order By: Relevance
“…We found that E. faecalis seems to be the dominant enterococcal species in poultry. Our results were consistent with the literature (15). In opposition to other authors, we isolated E. cecorum more often, and more rarely E. faecium, E. hirae, E. gallinarum.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We found that E. faecalis seems to be the dominant enterococcal species in poultry. Our results were consistent with the literature (15). In opposition to other authors, we isolated E. cecorum more often, and more rarely E. faecium, E. hirae, E. gallinarum.…”
Section: Resultssupporting
confidence: 91%
“…Among other poultry species, strains originated from turkeys (23.4%; 548/2337), geese (2.1%; 50/2337) and ducks (0.7; 16/2337). Similarly to other studies (15), in our study the most positive samples for enterococci were in broilers. In poultry, 9 of the most frequent identified species were E. faecalis (42.5%) > E. cecorum (7.9%) > E. faecium (4.4%) > E. hirae (2.7%) > E. gallinarum (2.2%) >E. casseliflavus (0.6%) > E. durans (0.2%) > E. avium (0.16%) > E. aquimarinus (0.04%).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Although enterococci are usually thought to be harmless commensals, they can also act as opportunistic pathogens. In recent years, their increased role has been noted in poultry and pigeon pathology [6][7][8][9]. According to the literature the drug-resistance of the bacteria isolated from pigeons may be very high [4,10].…”
Section: Introductionmentioning
confidence: 99%
“…Multidrug-resistant enterococci have emerged as a global threat to public health, and vancomycin-resistant enterococci (VRE) currently rank among the leading bacterial causes of nosocomial infections. Although several studies reported the antibiotic resistance in avian Enterococcus [8,11,12] and the enterococcal virulence factors in humans, poultry, farm animals and wildlife, food, environment [11,[13][14][15][16][17], so far little is known about the antimicrobial susceptibility of enterococci from pigeons [4,18]. Moreover the occurrence of virulence factors has not been described among Enterococcus spp.…”
Section: Introductionmentioning
confidence: 99%